Candida biofilm formation on voice prostheses. Issue 3 (March 2015) - Talpaert, Moira J.; Balfour, Alistair; Stevens, Sarah; Baker, Mark; Muhlschlegel, Fritz A.; Gourlay, Campbell W.
Abstract : Laryngopharyngeal malignancy is treated with radiotherapy and/or surgery. When total laryngectomy is required, major laryngeal functions (phonation, airway control, swallowing and coughing) are affected. The insertion of a silicone rubber voice prosthesis in a surgically created tracheoesophageal puncture is the most effective method for voice rehabilitation. Silicone, as is the case with other synthetic materials such as polymethylmethacrylate, polyurethane, polyvinyl chloride, polypropylene and polystyrene, has the propensity to become rapidly colonized by micro-organisms (mainly Candida albicans ) forming a biofilm, which leads to the failure of the devices. Silicone is used within voice prosthetic devices because of its flexible properties, which are essential for valve function. Valve failure, as well as compromising speech, may result in aspiration pneumonia, and repeated valve replacement may lead to either tract stenosis or insufficiency. Prevention and control of biofilm formation are therefore crucial for the lifespan of the prosthesis and promotion of tracheoesophageal tissue and lung health. To date, the mechanisms of biofilm formation on voice prostheses are not fully understood. Further studies are therefore required to identify factors influencing Candida biofilm formation. This review describes the factors known to influence biofilm formation on voice prostheses and current strategies employed to prolong their life by interfering with microbial colonization. Abbreviations: QAS, quaternary ammonium salt; TL, total laryngectomy; VP, voice prosthesis.